2021
DOI: 10.3390/cancers13164111
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Changes Induced in Melanoma by Cell Culturing in 3D Alginate Hydrogels

Abstract: Alginate hydrogels have been used as a biomaterial for 3D culturing for several years. Here, gene expression patterns in melanoma cells cultivated in 3D alginate are compared to 2D cultures. It is well-known that 2D cell culture is not resembling the complex in vivo situation well. However, the use of very intricate 3D models does not allow performing high-throughput screening and analysis is highly complex. 3D cell culture strategies in hydrogels will better mimic the in vivo situation while they maintain fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…From a clinical perspective, Kappelmann-Fenzl et al investigated EGR1-stained tissue sections, finding that EGR1 could be detected in most melanoma cells [31]. The authors further noted an absence of EGR1 protein expression in benign melanocytes, weak cytoplasmic staining in melanoma cells from primary tumor, and intense nuclear staining in melanoma metastasis, suggesting an association between increasing EGR1 expression and melanoma progression [31]. Kanemaru et al similarly found increased EGR1 expression in tumor tissues from patients with invasive melanoma compared to tissues of noninvasive melanoma [32].…”
Section: Discussionmentioning
confidence: 99%
“…From a clinical perspective, Kappelmann-Fenzl et al investigated EGR1-stained tissue sections, finding that EGR1 could be detected in most melanoma cells [31]. The authors further noted an absence of EGR1 protein expression in benign melanocytes, weak cytoplasmic staining in melanoma cells from primary tumor, and intense nuclear staining in melanoma metastasis, suggesting an association between increasing EGR1 expression and melanoma progression [31]. Kanemaru et al similarly found increased EGR1 expression in tumor tissues from patients with invasive melanoma compared to tissues of noninvasive melanoma [32].…”
Section: Discussionmentioning
confidence: 99%
“…The gene early growth response 1 (EGR1) was the most notable upregulated gene in melanoma, with a 3-fold increase in mRNA expression compared to primary melanocytes. This highlighted the importance of EGR1 in melanoma progression ( Kappelmann-Fenzl et al, 2021 ).…”
Section: The Importance Of Viscosity On the Spreading And Migration O...mentioning
confidence: 93%
“…To confirm that the isolated cells are from melanocytic origin, GRM1 expression was verified by RT-PCR, as previously described [ 23 ] (Supplementary Figure S1 ). Human melanoma cell lines Mel Juso, 501Mel, and Mel Im (FUCCI) were cultivated as indicated elsewhere [ 24 , 25 ]. Mycoplasma contamination was regularly excluded for all primary cells and cell lines.…”
Section: Methodsmentioning
confidence: 99%
“…The FUCCI (fluorescence ubiquitination-based cell cycle indicator)-labelled Mel Im cells were generated and quantified as described previously [ 24 ].…”
Section: Methodsmentioning
confidence: 99%